2022
DOI: 10.1103/physreve.106.055208
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of highly charged plasmas with multicomponent 1+ ion injection

Abstract: We establish multicomponent 1+ injection into a charge breeder electron cyclotron resonance ion source and an associated computational procedure as a noninvasive probe of the electron density n e , average electron energy E e , and the characteristic times of ionization, charge exchange, and ion confinement of stochastically heated, highly charged plasma. Multicomponent injection allows refining the n e , E e ranges, reducing experimental uncertainty. Na/K injection is presented as a demonstration. The E e and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…In an ECRIS plasma, the temporal evolution of the ion density of a given charge state n q i (q being the charge state) is described by a set of coupled non-linear differential equations, called balance equations, that take into account three dominant processes: i) step-by-step ionization by electron impact, ii) charge exchange and iii) diffusion or transport. If plasma is assumed to be in dynamic equilibrium, balance equations can be written as follows [14,15,16]:…”
Section: Theoretical Approachmentioning
confidence: 99%
“…In an ECRIS plasma, the temporal evolution of the ion density of a given charge state n q i (q being the charge state) is described by a set of coupled non-linear differential equations, called balance equations, that take into account three dominant processes: i) step-by-step ionization by electron impact, ii) charge exchange and iii) diffusion or transport. If plasma is assumed to be in dynamic equilibrium, balance equations can be written as follows [14,15,16]:…”
Section: Theoretical Approachmentioning
confidence: 99%
“…Typical uncertainties of high charge state potassium confinement and charge exchange times are 100-200% while the ionization times can be estimated more accurately, i.e. with 40-70% relative uncertainty [18][19][20][21], which raises the concern that the CT method might not be able to detect small variations of the plasma parameters. Thus, the statistical relevance of the measurement results presented above could be questioned.…”
Section: Figmentioning
confidence: 99%
“…It has been shown that the inherent uncertainties of the CT method can be reduced e.g. by two-component injection or overlapping the (⟨E e ⟩ , n e ) solution sets of neighbouring charge states albeit with the caveat of additional assumption [20]. Furthermore, it has been demonstrated that the main contributor to the large relative uncertainty of the CT method is the lack of precise ionization cross section data whereas the presumed EED has a smaller effect [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation